The Associations of Multimorbidity With Health-Related Productivity Loss in a Large and Diverse Public Sector Setting: A Cross-Sectional Survey. Issue 6 (June 2018) - Wang, Lili; Cocker, Fiona; Kilpatrick, Michelle; Otahal, Petr; Si, Lei; Palmer, Andrew J.; Sanderson, Kristy
Abstract : Objective: To evaluate absenteeism, presenteeism, and total lost productive time (LPT) associated with multimorbidity. Methods: Cross-sectional data from 3228 state-government employees from Tasmania were collected in 2013. The validated measures of absenteeism, presenteeism, and LPT were obtained from employees' self-reported data over a 28-day period. Analyses were stratified by sex. Negative binomial models were used to estimate the associations between multimorbidity and LPT. Results: The average health-related total LPT was 1.2 (standard deviation [SD] = 2.4) and 1.7 (SD = 3.5) days for men and women with multimorbidity, respectively. Women (rate ratio [RR] = 2.9, 95% confidence interval [CI] 1.8 to 4.9) and men (RR = 4.4, 95%CI 3.0 to 6.2) with 4+ chronic conditions were significantly more likely to report LPT compared with those without any chronic conditions. Conclusion: We found multimorbidity is of concern within the workforce, with a positive association of multimorbidity and LPT observed, and significant differences in LPT between men and women reporting multimorbidity.